Tantangan dan Solusi Guru PAK dalam Menerapkan Pembelajaran PAK melalui Pendekatan Deep Learning - Sergius Lay (Jurnal Magistra, 2025)
This study examines the challenges and solutions faced by teachers in implementing Catholic Religious Education (CRE) learning through a deep learning approach in the classroom. The era of educational digitalization demands a transformation from traditional learning methods to more innovative and profound approaches. Deep learning in the educational context refers to learning strategies that encourage students to understand concepts deeply, analyze, evaluate, and integrate knowledge with spiritual experiences. This research methodology uses a literature review by analyzing various literature sources related to the implementation of deep learning in CRE learning. The research results show that teachers face main challenges in the form of limited technological competence, resistance to learning paradigm changes, and infrastructure inadequacy. Solutions that can be applied include improving teacher digital literacy, developing hybrid learning models, integrating technology that is in accordance with Catholic values, and forming professional learning communities. This research contributes to developing an implementation framework for effective and meaningful deep learning for CRE learning. Practical implications include policy recommendations for teacher professional development and phased implementation strategies in the context of Indonesian Catholic education.